Uji Efektivitas Seduhan Kopi Biji Okra (Abelmoschus esculentus) terhadap Penurunan Kadar Glukosa Darah pada Mencit yang diinduksi Aloksan - Zulvia Faridatul Munawaroh; Rahmat A.H. Wahid; Nurul Marfu'ah (University Of Darussalam Gontor, 2019)
Diabetes mellitus is a degenerative disease characterized by high blood glucose levels. Various ways that people use for treatment, herbal is one of the choices. God will not create an illness unless Him has created the medicine. One of the plants that is often used to treatment diabetes mellitus is okra plants. Okra seeds could be processed into coffee which is used as a substitute for caffeinated coffee. Based on community experience, so this research to know the effectiveness test of steeping coffee from okra (Abelmoschus esculentus) seeds in alloxan-induced diabetic mice and to know the effective concentration of steeping coffee from okra (Abelmoschus esculentus) seeds in alloxan-induced diabetic mice. This research was an experimental study. The research design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications. The sample consisted of 16 male mice. The study was divided into 4 groups, The sample consisted of16 male mice and divided into 4 group, giving aquadest as a positive control (PC) while in treatment T1 by giving steeping coffee from okra seeds with a concentration of 1.82 mg/grBW/day, 3.64 mg/grBW/day for T2 and T3 with a concentration of 5.46 mg/mgBW/day for 10 days . Data were analyzed using the SPSS 16.0. According to the results of the One Way ANOVA test with a significance level of 95% were obtained at 0,000 (p = <0.05) which means that, between treatments given by okra seeds coffee, okra seeds coffee were effective against blood glucose levels of mice after alloxan was induced. Based on the three treatments for the administration of okra seeds coffee with various concentrations, group T3 (5.46 mg/mgBW/day) with a significance value of 0,000 (p<0.05) which was the most effective for reducting blood glucose levels in alloxan-induced diabetic mice.